THE CULTURE IDENTITY OF INDONESIAN IN A MOVIE OF RAYA AND THE LAST DRAGON - Fiona Puspitasari Mulyadi; Luthfi Nasiroh Khoirun; Marginingsih Marginingsih (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
Culture is a part and identity of a country that owns it, in Raya animation which is a Disney-made animation made by combining cultures from Southeast Asia. The movie Raya and the Last Dragon can be a means to reflect on the values and perspectives of life related to aspects of locality. This movie also talks about various cultures. Therefore, this research aims to find Indonesia's cultural identity and the message conveyed from the movie with the title "Raya and the Last Dragon." This research was conducted using the qualitative descriptive method, data from various sources to gain a deeper understanding, and data from the UNESCO World Cultural Heritage List. The primary source of data in this research is the movie "Raya and the Last Dragon." And the results of the data found by researchers are 10 cultures belonging to Indonesia, namely the Roof of Rumah Gadang, Batik Culture, Keris, Gamelan, Wayang, Batik Mega Mendung, Indonesian Food, Pawancarno Gebyok, Caping, and Unity in Diversity. Five of the 10 cultures found have been listed on UNESCO's World Cultural Heritage list.